Pengaruh Model Pembelajaran Predict Observe Explain dan Motivasi terhadap Higher Order Thinking Skills Siswa : (The Effect of Predict Observe Explain Learning Model and Motivation on Students' Higher Order Thinking Skills) - Nurfadilah Nurfadilah; Revis Asra; Syaiful Syaiful (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
The low thinking ability of students can be caused by the strategies and models applied by the teacher in learning that have not been oriented towards empowering high-level thinking, and only emphasize understanding concepts (Kawuwung, 2014). Therefore, to increase the HOTS of students, a good learning strategy is needed, starting from the selection of the learning model used in the classroom. The learning model that makes students active is the POE (Predict, Observe, Explain) The strength of this research POE provides an opportunity for students to generate their own conceptual knowledge through reconciliation and negotiation between prior knowledge and new knowledge. Weaknesses in this study Requires readiness and skills from teachers and students, Requires readiness and careful planning in addition to requiring quite a long time.learning model. This study aims to determine the effect of using the Predict Observe Explain learning model, and motivation on students' HOTS in the biology subject matter of the human respiratory system. This research is a quantitative research. The design used in this study is a quasi-experimental design. There are two types of instruments used as a means of collecting data (learning motivation questionnaire and learning test). The instrument used has been validated first by the validator. The results showed that the results of the control class with the pretest average were 68.90, the posttest was 72.65, while the pretest experimental class was 71.40, while the posttest was 79.45. The relationship between POE and HOTS is significant and positive at 13,892. Based on the results of calculations with the SPSS program, the value of sig <0.05 was obtained, namely 0.000 or 0.000 <0.05 so that Ho was rejected and Ha was accepted. Learning motivation also has a significant effect on the HOTS ability of class VIII students of SMPN 9 Merangin, with the acquisition of sig <0.05, namely 0.001 or 0.000 <0.05 so that Ho is rejected and Ha is accepted. Meanwhile, the relationship between the two is positive and significant at 12,527. So the use of the POE Model and learning motivation contributed to the improvement of the HOTS Ability of VIII students of SMPN 9 Merangin. Abstrak. Rendahnya kemampuan berpikir peserta didik dapat disebabkan karena strategi dan model yang diterapkan oleh guru dalam pembelajaran belum berorientasi pada pemberdayaan berpikir tingkat tinggi, dan hanya menekankan pada pemahaman konsep (Kawuwung, 2014). Oleh karena itu, untuk meningkatkan HOTS peserta didik diperlukan strategi pembelajaran yang baik, dimulai dari pemilihan model pembelajaran yang digunakan dalam kelas. Model pembelajaran yang membuat siswa aktif adalah model pembelajaran POE (Predict, Observe, Explain). Penelitian ini bertujuan untuk Mengetahui pengaruh penggunaan model pembelajaran Predict Observe Explain, dan motivasi terhadap HOTS siswa pada mata pelajaran biologi materi sistem pernapasan manusia. Penelitian ini merupakan penelitian kuantitatif. Desain yang digunakan dalam penelitian ini adalah eksperimen semu (Quasi Experimental Design). Instrumen yang digunakan sebagai alat pengumpulan data ini ada dua jenis (angket motivasi belajar dan tes belajar). Instrumen yang digunakan terlebih dahulu telah divalidasi oleh validator. Hasil penelitian menunjukkan bahwa hasil kelas control dengan rata-rata pretest yakni 68,90,posttest yakni 72,65, sedangkan kelas eksperimen pretest yakni 71,40, sedangkan posttest yakni 79,45. Hubungan antara POE dan HOTS signifikan dan positif sebesar 13,892. Berdasarkan hasil perhitungan dengan program SPSS, diperoleh nilai sig < 0,05 yaitu 0,000 atau 0,000 < 0,05 sehingga Ho ditolak dan Ha diterima. Motivasi belajar juga berpengaruh signifikan terhadap kemampuan HOTS siswa kelas VIII SMPN 9 Merangin, dengan perolehan nilai sig < 0,05 yaitu 0,001 atau 0,000 < 0,05 sehingga Ho ditolak dan Ha diterima. Sedangkan hubungan antara keduanya adalah positif dan signifikan sebesar 12,527. Jadi Penggunaan Model POE dan motivasi belajar memberikan kontribusi terhadap peningkatan Kemampuan HOTS siswa VIII SMPN 9 Merangin.